2009
DOI: 10.1099/mic.0.022251-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcium in acclimation of the cyanobacterium Synechococcus elongatus PCC 7942 to nitrogen starvation

Abstract: A Ca2+ signal is required for the process of heterocyst differentiation in the filamentous diazotrophic cyanobacterium Anabaena sp. PCC 7120. This paper presents evidence that a transient increase in intracellular free Ca2+ is also involved in acclimation to nitrogen starvation in the unicellular non-diazotrophic cyanobacterium Synechococcus elongatus PCC 7942. The Ca2+ transient was triggered in response to nitrogen step-down or the addition of 2-oxoglutarate (2-OG), or its analogues 2,2-difluoropentanedioic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 42 publications
(70 reference statements)
0
28
0
Order By: Relevance
“…Intracellular Calcium Dynamics. Cyanobacteria show a very tight regulation of Ca 2+ i levels, typically in the low nanomolar range (15,20,21), but Ca 2+ pumping in euendoliths could potentially create transient or even continued intracellular hyperaccumulation (10). We used several approaches to probe Ca 2+ i in strain BC008.…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular Calcium Dynamics. Cyanobacteria show a very tight regulation of Ca 2+ i levels, typically in the low nanomolar range (15,20,21), but Ca 2+ pumping in euendoliths could potentially create transient or even continued intracellular hyperaccumulation (10). We used several approaches to probe Ca 2+ i in strain BC008.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a 2DE proteomic analysis showed that the synthesis of EF-Tu is affected by Ca 2+ levels [43]. ] i levels have been more frequently studied in E. coli and cyanobacteria [13][14][15]19], limited studies have been done in B. subtilis. Our results indicate that indeed B. subtilis tightly controls cytosolic calcium and we concur with other studies [16] in that intracellular calcium levels regulate the expression of many genes and the synthesis of proteins.…”
Section: Camentioning
confidence: 99%
“…Indirect evidence suggests that Ca 2+ may play a role in various bacterial physiological processes such as spore formation, chemotaxis, heterocyst differentiation, transport and virulence [9][10][11][12]. Several reports have shown that bacteria are capable of maintaining intracellular Ca 2+ homeostasis, and Ca 2+ transients are produced in response to adaptation to nitrogen starvation, environmental stress [13][14][15][16], and metabolites of carbohydrate metabolism [17,18]. These findings suggest a regulatory role for Ca 2+ in bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ is a part of a hyperinflamatory host response to bacterial infection, and accumulates in airway epithelia, pulmonary and nasal liquids of CF patients [10], [11]. There is growing evidence suggesting that Ca 2+ also plays a significant role in the physiology of certain bacteria, affecting maintenance of cell structure, motility, chemotaxis, cell division and differentiation, gene expression, transport, and spore formation [12], [13], [14], [15], [16]. Several bacteria including P. aeruginosa have been shown to maintain intracellular Ca 2+ at sub-micromolar levels and produce Ca 2+ transients in response to environmental and physiological factors [17][19].…”
Section: Introductionmentioning
confidence: 99%